Effect of the route of administration on the mucosal and systemic immune responses to Lawsonia intracellularis vaccine in pigs. Issue 4 (April 2015) - Nogueira, MG; Collins, AM; Dunlop, RH; Emery, D
Abstract : In an on‐farm study, 40 weaned piglets aged 3 weeks were vaccinated with Lawsonia intracellularis vaccine orally, IM or IP while a fourth group remained unvaccinated. All vaccinated animals showed increased serum levels of L. intracellularis ‐specific IgG antibodies, but significantly elevated concentrations of specific IgG, IgA and cytokines were generated in ileal mucosal secretions from the orally and IP vaccinated pigs when examined at 17 days after vaccination.